\(\dfrac{x-1}{3}-\dfrac{1}{8}=\dfrac{5}{8}\Rightarrow\dfrac{x-1}{3}=\dfrac{6}{8}=\dfrac{3}{4}\)
\(\Rightarrow4.\left(x-1\right)=3.3\Rightarrow4x-4=9\)
\(\Rightarrow4x=13\Rightarrow x=\dfrac{13}{4}\)
\(\dfrac{x-1}{3}-\dfrac{1}{8}=\dfrac{5}{8}\\ \dfrac{x-1}{3}=\dfrac{5}{8}+\dfrac{1}{8}=\dfrac{3}{4}\\ x-1=\dfrac{3}{4}\cdot3=\dfrac{9}{4}\\ x=\dfrac{9}{4}+1=\dfrac{13}{4}\)
\(\dfrac{x-1}{3}-\dfrac{1}{8}=\dfrac{5}{8}\\ \Leftrightarrow8\left(x-1\right)-3=15\\ \Leftrightarrow8x-8-3=15\\ \Leftrightarrow8x-11=15\\ \Leftrightarrow8x=15+11\\ \Leftrightarrow8x=26\\ \Leftrightarrow x=\dfrac{13}{4}\)
Vậy....